Radiation‐induced rhinosinusitis: Mechanism research and clinical progress review - Chunge Zheng; Longgang Yu; Yan Jiang (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objectives Radiation‐induced rhinosinusitis is a vital dose‐limiting reaction in patients with head and neck malignancy. Unlike oral mucositis during or after radiotherapy, radiation‐induced sinusitis is easily overlooked in clinical practice and rarely included in experimental studies. Herein, we review the literature to date on radiation‐induced rhinosinusitis. Methods Relevant studies published between 1995 and 2022 were determined through a detailed search using open keywords from PubMed, with manual search of the reference list of the identified articles. Keywords searched were “ionizing radiation,” “radiotherapy,” “intensity‐modulated radiotherapy,” “head and neck tumor,” “nasopharyngeal carcinoma,” “nasal epithelium,” “radiation damage,” and “radiation‐induced rhinosinusitis.” Full‐text articles that clearly stated the pathogenesis, clinical manifestation, predictors, treatment, and prognosis of radiation‐induced rhinosinusitis were included. Results Radiation‐induced rhinosinusitis occurs during radiotherapy and can last for months or even years after radiotherapy. A mixture of cellular outcomes caused by ionizing radiation and persistent damage of the epithelial and submucosal tissues after the treatment result from the radiotherapy itself. Endoscopic sinus surgery improves symptoms but can be accompanied by intraoperative and postoperative complications. Nasal irrigation, steroids, and antibiotics appear to reduce inflammation and relieve symptoms to a certain extent. Studies on other potentially useful drugs are underway and in the exploration stage, without clinical application. Conclusions Despite its high incidence, radiation‐induced rhinosinusitis is a type of dose‐limiting toxicity that theoretically does not produce fatal effects at controlled doses and with adequate follow‐up care. In moderate‐to‐severe cases, toxicity may be present. Currently, radiation‐induced rhinosinusitis has potential prevention and treatment strategies. However, no unified management protocol has shown significant improvement in radiation‐induced rhinosinusitis. Further research is necessary.